(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
Training in driving in foreign countries has its own characteristics, to identify which we turned to the analysis of methods and techniques for teaching driving in the UK. The article analyzes the system of training drivers of motor vehicles, teaching driving in foreign countries. The features of driving in the UK are revealed.